Revision of the French Terebellidae sensu stricto (Annelida, Terebelliformia), with descriptions of nine new species - Lavesque, Nicolas; Daffe, Guillemine; Londoño-Mesa, Mario H.; Hutchings, Pat (Zootaxa, 2021)
This work is the last of four papers of the Spaghetti Project, aiming to revise the species of terebellids, a.k.a. “spaghetti” worms, present in the European French waters. In this last paper the Terebellidae, sensu stricto, from French waters are revised based, on material available in the French marine stations, type materials stored in the MNHN collection and newly collected specimens. Nine new species are described using both morphological and molecular tools: Eupolymnia gili n. sp., E. lacazei n. sp., E. meissnerae n. sp., Lanice kellyslateri n. sp., Paramphitrite dragovabeci n. sp., Pista labruneae n. sp., P. miosseci n. sp., P. sauriaui n. sp., and Terebella banksyi n. sp. European species of Eupolymnia are distinguished mainly by the shape of the lateral lobes and the size of the branchial stems. The two species belonging to Lanice genus are distinguished by the fusion of the first ventral shields, the shape of both noto- and neuropodia, and the pigmentation of the upper lip. The two species of Paramphitrite are distinguished by the presence or absence of a medial dorsal gap between the pairs of branchiae, by the shape of the lateral lobes and the presence or absence of a nephridial papilla on segment 4. The different species of Pista are distinguished by the number of pairs of branchiae, the shape of the lateral lobes and uncini. Finally, the two species of Terebella are distinguished by the number of segments with nephridial and genital papillae and the segments on which the branchiae occur. An identification key for European species of Terebellidae sensu stricto is also provided.